A COMPARATIVE STUDY OF TUBERCULOSIS KNOWLEDGE LEVELS BETWEEN MEDICAL AND BUSINESS ECONOMICS STUDENTS AT YARSI UNIVERSITY - Putri, Kintari Dimiano; Damayanti, Ndaru Andri; Ferlianti, Rika (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis, which has been recognized as a global health emergency by the World Health Organization (WHO). Despite widespread prevention and treatment programs, tuberculosis control continues to face challenges, particularly due to insufficient public knowledge about effective preventive measures. This study aims to compare the level of knowledge about tuberculosis between medical students and business economics students at Yarsi University. This study used a descriptive comparative quantitative design involving 183 respondents, consisting of 121 medical students and 62 business economics students class of 2021. Data were collected using a questionnaire consisting of 11 questions related to tuberculosis and grouped into three knowledge categories: good, sufficient, lacking. Data were analyzed using the Mann-Whitney test due to abnormal data distribution. The results showed a significant difference in the level of knowledge about tuberculosis between the two groups (p < 0.05). Medical students showed a higher level of knowledge, with 100% being in the good category, compared to 75.8% in business economics students. This study highlights the importance of structured education in influencing knowledge levels and recommends targeted health education for non-medical students. This study confirms the role of education in raising awareness about tuberculosis and supports the integration of health knowledge into non-medical curricula to support public health.